MODEL PEMBERDAYAAN PEREMPUAN BERPERSPEKTIF EKOFEMINISME OLEH LEMBAGA NAWAKAMAL DI KECAMATAN DUKUN KABUPATEN MAGELANG - , MAULA PARAMITHA W, Dr. Agr. Sri Peni Wastutiningsih ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The issue of women's empowerment does not stop at the technical aspects but also deals with the critical awareness of current problems, one of them being food. For women, proximity to food is more than just a domestic affair due both to the complexity of food systems and the capitalist-patriarchal system that all women face. This study uses ecofeminist perspectives to examine the relationship between women and food through deconstruction of modern agricultural systems that are detrimental to both humans and nature. The focus of this research is based on the idea of âFrom the Backyard Towards Dining Tableâ which was created by the NGO Nawakamal, in Magelang regency Dukun District. The implementation of this idea can be used to illustatre womenâs empowerment through ecofeminism perspectives. This study uses the Mix-Method, which combines the qualitative approach of Structure-Lege-Technik to structure ideas of empowerment, and quantitative approach of surveys of 30 women empowerment targets to determine the success of the implementation of the idea. The purposes of this research were to construct the empowermentâs idea using ecofeminism perspectives and to find out it implementation during empowerment and construct it as a empowerment model. Analysis showed a connectivity between the idea of the aggregate of empowerment that modern agriculture impacts women, food and ecology. Thus, women need to strive for the right to healthy food and environmental sustainability by using environmentally friendly farming, which is begun in their own backyards. Ecofeminism perspectives hold the idea that masculinity in modern agriculture has caused violence against both humans and nature and that femininity can restore the farm for food (subsistence) and the help to preserve nature through the use of environmentally friendly farming. Empowerment models using the perspective of ecofeminism as a paradigmatic base, along with the implementation of technical training and FGDs, were conducted with a critical approach to education and media awareness in the form of booklets and film. The empowerment need a long time, thus its need a roadmap for technical and awarness goal